ANALISIS IDENTIFIKASI BAHAYA KECELAKAAN KERJA MENGGUNAKAN JOB SAFETY ANALUSIS (JSA) DENGAN PENDEKATAN HAZARD IDENTIFICATION, RISK ASSESSMENT AND RISK CONTROL (HIRARC) DI PT PNM CABANG SOLO - Febriansyah, Mohamad Dwiky; Indriastiningsih, Erna; Fajar Sutrisno, Agung Widiyanto (JURNAL ILMIAH EDUNOMIKA, 2024)
To minimize or eliminate workplace hazards that could lead to accidents, implementing effective risk management is essential whose activities focus on the process of systematic scientific identification, evaluation, and prioritization of risks. This research seeks to identify potential hazards and propose solutions to reduce them at PT PNM Solo Branch. A quantitative approach was employed, with data collected through observation and interviews with 3 resource persons, namely 1 Head of Account Officer division and 2 workers in Account Officer division at PT Permodalan Nasional Madani (PNM) Solo Branch. Data analysis was carried out the research utilized the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method alongside Job Safety Analysis (JSA). The findings revealed that within the three types of tasks performed by the Account Officer division, encompassing 11 activities, 29 occupational accident risks were identified that could occur with 4 potentials categorized into the Extremely level and 1 potential in the medium category. The solutions provided are in the form of implementing the use of PPE, checking vehicle engines optimally, making work SOPs, and also better structuring the workspace.